Developing and validating modular surveys for vector-borne diseases: A study protocol - Skyler Finucane; Alexandria Renault; Mary H. Hayden; Kacey Ernst; Sarah Yeo (PLoS ONE, 2025)
Vector-borne diseases are an increasing threat to human health and well-being in the United States. Understanding public perception and practices to reduce vector abundance and vector-human contact can guide effective interventions. Nevertheless, vector-borne disease surveys, which are widely used in the field to understand public perception and practices, are often inconsistent in terms of structure and implementation. This protocol is designed to provide guidance for public health professionals and researchers in the development of future knowledge, attitudes, and practices studies by ensuring uniformity in design and structure. This manuscript describes a rigorous three-phase protocol for the development of standardized vector-borne disease survey modules that can be used throughout the United States to generate data that are comparable across diverse regions. During phase one, a workshop with subject matter experts and a comprehensive literature review will be conducted to identify survey domains and generate items of interest. Survey items will also be mapped based on two theoretical frameworks: the Health Belief Model and the Risks, Attitudes, Norms, Abilities, and Self-Regulation framework. Standards across knowledge, attitudes, and practices surveys will enhance the analysis and interpretation of the data across geographies and time. During phase two, a group of expert judges will evaluate survey items based on content relevance, representativeness, and technical quality. During the final phase, cognitive interviews and surveys with target audience groups will be conducted to measure and ensure the face validity, reliability, and external validity of the modules. Participants will be drawn from a diverse range of educational backgrounds and geographic locations. The surveys developed through this protocol will facilitate acquisition of insights into the public’s knowledge, attitudes, and practices concerning vector-borne diseases, allowing for the collection of comparable data across various regions in the United States.